Exploring Demographic Properties and Amplification Efficiency of N and ORF-1ab Gene in Suspected COVID-19 Patients in Dhaka, Bangladesh - Sumaiya khatun; Md Moazzem Hossain; Md Zaforullah Chowdhury; Mamun Mia; Nazmun Nahar Munny; Fatima Tuj Johora (Update Dental College, 2022)
Background: In late December 2019, an outbreak of pneumonia with an unknown cause occurs in Wuhan, China. Later, the causative agent was identified as SARS-CoV-2. Early laboratory diagnosis plays an important role in any outbreak by cutting the spread of infection by isolating the infected person. Nucleic acid detection via PCR remains the gold standard because no alternative scientific method for detecting SARS-CoV-2 is available. Objective: The goal of this study was to learn more about the demographic characteristics of SARS-CoV-2-affected people and the sensitivity pattern of the N & ORF-1ab gene among them. Methods: A swab from the nasopharynx for nucleic acid detection was collected from 3183 SARS-CoV-2 suspected cases attending outdoors and indoors at Aichi Hospital and Japan East-West Hospital. Results: 649 (20.4%) were found PCR positive. Among the positive cases, the male was 478 (73.7%) and the female was 171 (26.3%), mean age was 40.35 ± 14.551 years, ranging from 4 - to 90 years. The highest prevalence of SARS-CoV-2 was identified in the 21-40 years old group (50.7%), followed by the 41-60 years old group (33.1%). The N gene was found to be 100% positive and ORF-1ab was 22.03% positive. Conclusion: According to the findings of this study, males and younger generations are at an elevated risk of contracting the virus, and maybe a source of infection for other family members. According to this study, the N gene has higher sensitivity and amplification efficiency than ORF-1ab. Update Dent. Coll. j: 2022; 12(1): 27-31